KEANEKARAGAMAN IKAN DI PERAIRAN SUNGAI LINGGANG, KABUPATEN BELITUNG TIMUR - Ria Erika; Kurniawan Kurniawan; Umroh Umroh (Akuatik: Jurnal Sumberdaya Perairan, 2018)
East Belitung regency is one of the regency which has a watershed area with the potential of fishery resources. This area is still classified as areas that have not yet done a lot of exploitation of fishery resources, especially freshwater fisheries. This study aims to analyze the fish diversity which contained in the Lenggang river, East Belitung Regency. The research was conducted on March 2017 in Lenggang River. This research used the purposive sampling method, on 3 stations of Lenggang River. The Sero fishing gear used for sampling of fish. The results obtained as many as 103 individuals at station 1 consists of 11 types which are grouped in 10 families, at station 2 as much as 466 individuals consists of 9 types grouped in 5 families, and then at station 3 contain the highest composition of fish is 538 individuals consisting of 8 types, which are grouped in 5 families. The fish diversity in Lenggang River ranged from 1,870 to 2,147 which are included in the criteria of medium diversity